2012
DOI: 10.1002/jbm.a.34095
|View full text |Cite
|
Sign up to set email alerts
|

Polyaspartamide‐polylactide electrospun scaffolds for potential topical release of Ibuprofen

Abstract: In this work, the production and characterization of electrospun scaffolds of the copolymer α,β-poly(N-2-hydroxyethyl)-DL-aspartamide-graft-polylactic acid (PHEA-g-PLA), proposed for a potential topical release of Ibuprofen (IBU), are reported. The drug has been chemically linked to PHEA-g-PLA and/or physically mixed to the copolymer before electrospinning. Degradation studies have been performed as a function of time in Dulbecco phosphate buffer solution pH 7.4, for both unloaded and drug-loaded scaffolds. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…However, the evaluation of degradation in that study occurred in PBS, but did not assay degradation in serum. 36 Our findings suggest that both the release properties of IBP and the degradation of the polymer differ in PBS versus serum containing solutions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the evaluation of degradation in that study occurred in PBS, but did not assay degradation in serum. 36 Our findings suggest that both the release properties of IBP and the degradation of the polymer differ in PBS versus serum containing solutions.…”
Section: Discussionmentioning
confidence: 73%
“…24 The chemical linking of IBP to α,β-poly(N-2-hydroxylethyl)-DL-aspartamide-graft-polylactic acid (PHEA-g-PLA) fibers also alters the release profile compared to the physical incorporation of the drug into fibers. 36 …”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that PHEA‐g‐PLA copolymer undergoes a degradation faster than PLA alone and it is able to prolong the release of a peptide drug, such as leuprolide. Furthermore, PHEA‐g‐PLA has been also used to prepare scaffolds for tissue engineering [14,15]…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we have performed electrospinning of PHEA‐g‐PLA copolymer and prepared fibrillar scaffolds where drug molecules have been linked to hydroxyl groups of PHEA …”
Section: Introductionmentioning
confidence: 99%